2024
DOI: 10.1109/tnnls.2023.3252569
|View full text |Cite
|
Sign up to set email alerts
|

SSGCNet: A Sparse Spectra Graph Convolutional Network for Epileptic EEG Signal Classification

Abstract: In this article, we propose a sparse spectra graph convolutional network (SSGCNet) for epileptic electroencephalogram (EEG) signal classification. The goal is to develop a lightweighted deep learning model while retaining a high level of classification accuracy. To do so, we propose a weighted neighborhood field graph (WNFG) to represent EEG signals. The WNFG reduces redundant edges between graph nodes and has lower graph generation time and memory usage than the baseline solution. The sequential graph convolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 54 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…We showed that the stability analysis offers a promising solution for performing the attention mechanism in a graph convolutional network faster and more efficiently by reducing the computational complexity, increasing the interpretability, and eliminating sensitivity to hyperparameters. Ranking the stability properties of nodes makes attention models more transparent and explainable and can be applied to a wide range of tasks, including weight pruning [41], sparsification, and reducing the number of non-zero weights in the network [42], making structural bias [43], etc.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the stability analysis offers a promising solution for performing the attention mechanism in a graph convolutional network faster and more efficiently by reducing the computational complexity, increasing the interpretability, and eliminating sensitivity to hyperparameters. Ranking the stability properties of nodes makes attention models more transparent and explainable and can be applied to a wide range of tasks, including weight pruning [41], sparsification, and reducing the number of non-zero weights in the network [42], making structural bias [43], etc.…”
Section: Discussionmentioning
confidence: 99%
“…EEG signal classification is a fundamental task in the analysis of brain function, which can be considered as one-dimensional biomedical signal processing [ 109 , 110 , 111 ]. Various processing methods can be employed to classify EEG signals, including statistics, machine learning (deep learning), and other techniques.…”
Section: The Pipeline Of Eeg Signal Analysismentioning
confidence: 99%